(3GdJNWjW GdGSJQGJjLj ddGJMGOGJ GdQjGVjI GdadSWjfjI dbWGY GdHWhdGJs - (3bTWI YeQ fUQ Gddgs ((3GdGScfOQjIs (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQs, 2004)
(3GdYedjGJ GdGOGQjI GdgGeI h GdMjhjI GdJj dgG ChdhjI Ydi HGbj GdYedjGJ GdCNQi ,ceG Cf ddJNWjW OhQ aj JMbjb HYV CgOGa GdGJMGOGJ GdQjGVjI GdadSWjfjI dbWGY GdHWhdI (B.s
Keywords: (3GdJQHjI GdHOfjI(B_(3GdGOGQI(B_(3adSWjfs